Aplikace měřicích sond v procesu obrábění - Kulhánek, Jaroslav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Cílem práce je aplikovat měřící sondy do procesu obrábění a prozkoumat možnosti využití těchto měřících sond. Pro praktickou část měření bylo použito měřících sond, programu dodávaného s měřícími sondami, obráběcího centra a výsledné data byly vyhodnoceny na PC. Závěrem práce je vyhodnocení měření a popsání vhodnosti aplikace.

The object of this work is to apply the measuring probe in the process of the machining and explore the use of the measuring probes. For the practical of the measurement was use measuring probes, the program supplied with the measuring probes, machining centers and the resulting data were evaluated on a PC. Finally, work is to evaluate the measurements and describe the appropriateness of the application.
Application of a measuring probes in milling proces
Keywords: Měřící sonda; dotykové sondy; bezdotykové sondy; optimalizace procesu obrábění; Measuring probe; touch probes; non-contact probes; optimalization machining process